It is crooked wood that shows the best sculptor - BETTY C MUBANGIZI (African Journal of Governance and Development, 2020)
As I write this editorial, #ZimbabweanLivesMatter has been trending on South Africa’s social mediaplatforms for close to 48 hours. Both local and international celebrities have spoken against humanrights abuses, said to be on the increase in that country. With the COVID-19 pandemic regulationsagainst social gatherings in full force, people have taken to social media to voice their displeasure.While politicians in the SADC region have, in the main, remained silent on the latest developmentsin that country, a growing civil society voice appears to be gaining traction with possibilities ofstraining international relations in the region. The issues in Zimbabwe are multifaceted; they cutacross several sectors, administrative regimes and political ideologies. Such issues are also notunique to Zimbabwe since many African countries have had their share of inefficiencies, abuse ofhuman rights and widespread public protests. This phenomenon encapsulates some of the issuesexplored in this July issue of the African Journal of Governance and Development.